Peran Self-Journaling Dalam Merefleksikan Kecintaan Pada Diri Sendiri Siswa Kelas XII Di SMAN 4 Purwokerto - Ardis Salsabila; Lutfi Faishol (STKIP PGRI SUMENEP, 2025)
This research aims to explore the role of self-journaling in helping class XII students at SMA N 4 Purwokerto understand themselves and increase self-love. In the context of the challenges faced by students, such as academic pressure and future demands, support from the surrounding environment and encouragement from within oneself become very important. Using descriptive qualitative methods, this research involved four students who had difficulty expressing themselves and showed low levels of self-love. Data was collected through interviews, observation and documentation, then analyzed to describe the student's self-reflection process. They begin to realize the importance of self-care and self-compassion in expressing love for themselves. The journaling process also helps students evaluate habits they want to change and design achievements they want to achieve in the next year. These findings show that self-journaling is not only a medium of expression, but also a tool to foster self-love through deep reflection, which in turn can improve students' emotional well-being.